1 John: 'Effects' in biblical texts that constitute 'lived experiences' in the contemplative reading of those texts - Merwe, Dirk G. van der (In die Skriflig, 2015)
It is evident according to 1 John 2:28–3:10 that the eschatological events predicted in this text have implications for how people should live prior to these events. This essay explores this eschatological pericope by analysing a number of the linguistic effects used in the text inorder to determine how the assumed spiritualities embedded in this pericope are generated to influence the readers. These linguistic effects form part of the rhetoric used by the author to awaken certain spiritualities (lived experiences) in readers in order to motivate them to act according to the recommendations given in the text. Four effects identified and examined in this essay that constitute ‘lived experiences’ in the contemplative reading of texts are (1) the dynamic interaction between text and reader, (2) the composition of images, (3) the dialectic of pretension and retention and (4) entanglement in a text. 1 Johannes: ‘Effekte’ in bybelste tekste wat ‘geleefde ervaringe’ in die nadenkende lees vandaardie tekste konstitueer. Volgens 1 Johannes 2:28–3:10 is dit duidelik dat die eskatologiese gebeure waarna daar in die teks verwys word, implikasies het vir hoe die mens vóór hierdie gebeure behoort te lewe. Die artikel ondersoek hierdie eskatologiese perikoop deur ‘n aantal van die taalkundige effekte in die teks te analiseer om vas te stel hoe die veronderstelde spiritualiteite wat in die perikoop ingebed is, gegenereer is. Hierdie taalkundige effekte vorm deel van die teksretoriek wat deur die outeur aangewend is om bepaalde spiritualiteite in lesers wakker te maak met die doel om hulle te motiveer om volgens die aanbevelings wat in die teks vervat is, te handel. Vier effekte wat in hierdie artikel geïdentifiseer en ondersoek word en wat spiritualiteite of ‘geleefde ervaringe’ deur die kontemplatiewe lees van tekste tot stand bring, is (1) die dinamiese interaksie tussen teks en leser, (2) die samestelling van beelde, (3) die dialektiek van pretensie en retensie en (4) ‘verstrengeling met ‘n teks.
free
Keywords: Bible. Epistle of John I; Christian life – Biblical teaching; Eschatology – Biblical teaching; Open access; Peer reviewed; Reading; Rhetoric in the Bible